(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2014)
The strategic design process and subsequent evaluation of results and their feedback and control are key moments in the management of an organization. This is therefore a topic of great relevance today in all publications in this subject area, especially empirical studies that provide both quantitative and qualitative information on the performance of companies in dynamic sectors such as tourism. That is why this article focuses on assessing the effectiveness of different strategies: generic, growth and diversification of a hotel company in the Caribbean area through the financial performance indicators and other qualitative. Results presented correspond to 100% of the study population, all of which made possible the information needed to detect major deviations from the strategic approach and possible alternatives for improving the performance and future competitiveness of the different facilities hotel. So empirical research of a tourist destination in growth and consolidation, as well as also a generalizable methodology for diagnosis and strategic design of organizations is provided.